Penetrasi Sosial dalam Persahabatan Mahasiswa Komunikasi dan Penyiaran Islam - Arbi, Armawati (Jurnal Askopis, 2017)
The competency of students can solve their problems in organisation that will increase their competencies of intrapersonal and interpersonal communication. Models of friendship and  models of conflcts of KPI students also portray their quotients.  Social penetration trained by family, organization, and enviroment. This research has found that  various friendship Models on KPI Students supports social penetration in Faculty Dakwah and Communication.  The constructive coflicts has supported  social penetration. In contrary,  the destructive conflict occured De-social penetration.  The factors increase social penetration that are the models of Friendship, a proud leader,  on time in meeting, loyalist, spirit, apreciation, and  educative sanctions. Social  penetration of students in organization has achieved Exchange Attitude layer In contrary, the factors  stimulated de-social penetration that are the destructive conflict, schedule organization were not running well because leader and some members were not commite and not consistent.  De- social penetration    back to orientation layer.  They  have withdrawn  communication when they have  undergone misunderstanding. Kompetensi mahasiswa dapat memecahkan masalahnya di organisasi, akan meningkatkan kompetensi komunikasi intrapribadi dan komunikasi antarpribadi. Model persahabatan dan konflik mahasiswa KPI akan menggambarkan kecerdasan mereka. Penetrasi sosial dilatih oleh keluarga, organisasi, dan lingkungan. Penelitian ini menemukan model-model persahabatan mahasiswa KPI di Fakultas Ilmu Dakwah dan ilmu Komunikasi yang mendukung penetrasi sosial. Faktor-faktor yang membangun penetrasi sosial, adalah  model keakrabanya, kagum terhadap pimpinan organisasi, jadwal rapat yang tepat,  loyal, semangat, penghargaan, dan saksi yang edukasi. Penetrasi sosial mahasiswa di organisasi  mencapai lapisan Menuju Pertukaran Sikap. (lapisan 2). Sebaliknya, faktor-faktor mendorong De- penetrasi sosial, adalah model konflik yang merusak, jadwal  yang tidak komitmen dan tidak konsisten. De-Penetrasi  sosial kembali ke lapisan awal. Mahasiswa memilih menarik diri  ketika  mereka mengalami salah paham.